2020
DOI: 10.1542/peds.2020-0628
|View full text |Cite
|
Sign up to set email alerts
|

Nickel Allergic Contact Dermatitis: Identification, Treatment, and Prevention

Abstract: Nickel is a ubiquitous metal added to jewelry and metallic substances for its hardening properties and because it is inexpensive. Estimates suggest that at least 1.1 million children in the United States are sensitized to nickel. Nickel allergic contact dermatitis (Ni-ACD) is the most common cutaneous delayed-type hypersensitivity reaction worldwide. The incidence among children tested has almost quadrupled over the past 3 decades. The associated morbidities include itch, discomfort, school absence, and reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 74 publications
0
18
0
2
Order By: Relevance
“…Nickel is the most frequently detected allergen in children worldwide, 81 responsible for 6% to 40% of positive patch tests (PPTs). 3,14,19,20,82,83 Sensitization is more common in children compared to adults, in North America compared to Europe, and in girls compared to boys.…”
Section: Metalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nickel is the most frequently detected allergen in children worldwide, 81 responsible for 6% to 40% of positive patch tests (PPTs). 3,14,19,20,82,83 Sensitization is more common in children compared to adults, in North America compared to Europe, and in girls compared to boys.…”
Section: Metalsmentioning
confidence: 99%
“…28,29 Because of the prevalence of nickel allergy, the European Union implemented a nickel directive in 1994 to regulate the release of nickel in consumer products to less than 0.5 g/cm 2 /week. 92 Since then, the frequency of nickel allergy has declined in adults and children in Europe. 93 Cobalt is often compounded with nickel and is thus also found in metal-plated products such as jewelry, belt buckles, and zippers.…”
Section: Metalsmentioning
confidence: 99%
“…Investigations also indicated that 1.1. Millions of American children are potentially allergic to nickel (13). It has also been reported that 8% to 10% of children and adolescence in the European general population present nickel allergy (14); however, this prevalence was about 23.7% in the children of North America between 1994 to 2014 (15).…”
Section: Contextmentioning
confidence: 99%
“…These scenarios usually can be diagnosed by the astute clinician without patch testing; however, the source of exposure may be less obvious if the nickel-releasing item has intermittent contact with the skin (eg, coins in the pocket, furniture hardware, personal grooming devices). 13 Other reported exposures include facial dermatitis from mobile phones, dermatitis of the ulnar hands from laptop use, and hand dermatitis from gaming controllers, [14][15][16] perhaps another reason for some to unplug.…”
Section: Clinical Presentationmentioning
confidence: 99%